The Rhetorical Structure of Review Article Abstracts in Applied Linguistics Published in High-Impact International Journals - Seth Soy; Safnil Arsyad; Syafryadin Syafryadin (Universitas Sanata Dharma, 2023)
It is generally acknowledged that an abstract is just a short text, but it is a gateway to publish and promote the article. However, writing a good abstract to publish in a prestigious international journal is quite challenging. Therefore, writing a well-constructed abstract based on the guideline is the best solution for writers. So far, the study on how to arrange rhetorical moves for writing the abstract of the review article is very limited. In this regard, this study aims to investigate the rhetorical structure of review article abstracts in applied linguistics published in high-impact international journals. The checklist obtained from the pilot project was used to analyze the 50 review article abstracts selected from four international journals. The results show that five moves are identified: Background, Objective, Method, Synthesis of Discussion, and Conclusion. The first two moves are regarded as conventional, while the rest of the moves are optional. Moreover, the outcomes indicate that some moves are constructed differently in terms of the content and structure, especially the linguistic features, compared to the research article abstracts. The findings also reveal that Background-Objective-Synthesis of Discussion (M1-M2-M4) is the common move pattern. As a practical implication, article writers should follow the common rhetorical move pattern and linguistic features as shown by this study when writing a review article abstract. For theoretical application, this study can be used to support future studies also.